2008
DOI: 10.1097/iae.0b013e318160798f
|View full text |Cite
|
Sign up to set email alerts
|

Idiopathic Choroidal Neovascularization as an Early Manifestation of Inflammatory Chorioretinal Diseases

Abstract: These findings suggest that ICNV can be an early manifestation of inflammatory chorioretinal diseases, including MEWDS, MFC, and PIC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
20
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 26 publications
2
20
0
3
Order By: Relevance
“…1,2 Type 2 neovascularization is associated with conditions such as age-related macular degeneration, myopic macular degeneration, angioid streaks, and punctate inflammatory choroidopathy (PIC)/multifocal choroiditis (MFC). [3][4][5][6] In young myopic patients, it is sometimes difficult to distinguish inflammatory choroidal neovascularization (CNV) from idiopathic or myopic CNV. We have identified a distinctive optical coherence tomography (OCT) finding that may help distinguish inflammatory CNV from the other causes of subneurosensory neovascularization.…”
mentioning
confidence: 99%
“…1,2 Type 2 neovascularization is associated with conditions such as age-related macular degeneration, myopic macular degeneration, angioid streaks, and punctate inflammatory choroidopathy (PIC)/multifocal choroiditis (MFC). [3][4][5][6] In young myopic patients, it is sometimes difficult to distinguish inflammatory choroidal neovascularization (CNV) from idiopathic or myopic CNV. We have identified a distinctive optical coherence tomography (OCT) finding that may help distinguish inflammatory CNV from the other causes of subneurosensory neovascularization.…”
mentioning
confidence: 99%
“…In this study, 43.9% of patients had ICNV, and 63.6% of them were female. Although it is not known why more female patients had ICNV, a study reported that ICNV is an early stage of inflammatory chorioretinal diseases, such as PIC, MCP, and MEWDS [19], which might partially explain the phenomenon. Moreover, there were only 4 patients (1.8%) with bilateral ICNV in this study, which indicated that patients with ICNV usually had unilateral CNV, and they appeared to have a low risk of developing CNV in their other eye [3].…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6][7][8][9][10][11] Olguların yaklaşık olarak %50'sinde vitreusta hücre olabileceği ancak ön kamarada hücrenin genellikle olmadığı bilinmektedir. 3 Bu olguda ise önce ön kamara hücrelerinin hemen sonrasında da vitreus hücre-leri ve tipik retina lezyonlarının ortaya çıktığı atipik başlangıçlı bir multipl geçici beyaz nokta sendromu olgusu sunulmaktadır.…”
Section: Discussionunclassified
“…Literatürde ileri yaş başlangıçlı, bilateral, tekrarlayıcı, koroid neovasküler membran oluşu-muna neden olan, multifokal koroidit veya akut idiyopatik kör nokta genişlemesi sendromu ile birlikte ortaya çıkan ve karakteristik beyaz noktaların görülmediği atipik olgular sunulmuştur. [4][5][6][7][8][9][10] Çalışmamızda, prodromal dönemde ön üveit tanısı konulup takibinde multipl geçici beyaz nokta sendromu bulguları ortaya çıkan atipik başlangıçlı bir olgu sunulmuştur.…”
unclassified